“What Do I Need That For?”: The Misalignment of Masculinity and College Preparation in an Urban School - Kolluri, Suneal (Urban education (Beverly Hills, Calif.), 2025)
Young Black and Latino men face profound academic obstacles in transitioning to college. Few studies have interrogated college readiness practices in urban schools through the lens of masculinity. Drawing on a yearlong ethnography, this study investigated how young men respond to college-readiness practices while enacting masculinity. Many young men were not convinced that working hard in their classes was necessary for their college futures. College preparation stressed seriousness and vulnerability, but masculine intellectualism was playful and tough. The contrast implies the need for college readiness practices better aligned with common experiences of masculinity in urban contexts.